PENERAPAN APLIKASI ACCURATE DALAM PENGINPUTAN TRANKSAKSI KAS DAN BANK DI PT. ICON SPIRIT INDONESIA - Vicky Maulana; Fitri Komariyah (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Icon Spirit Interior is one of the interior design contractors operating in East Java. PT. Icon Spirit is trusted to handle interior design for homes, apartments, villas, offices, shops, showrooms, coworking spaces, restaurants, cafes, clinics, karaoke rooms, pharmacies, libraries, music studios, hotels, with modern, simple minimalist, industrial, contemporary, elegant, traditional, to classic interior design themes. This research method uses a qualitative descriptive method with a case study approach that occurs within the company, which is carried out periodically to collect, process, and conclude existing data. This study aims to determine the flow of cash and bank transaction input at PT. Icon Spirit Indonesia, along with knowing what documents are needed for the correct cash and bank transaction input process. Keywords: accurate, cash and bank, accounting system